Високоміцний чавун зі зміцненим кремнієм та нікелем α-твердим розчином - Бубликов, В.Б.; Нарівський, А.В.; Бачинський, Ю.Д.; Ясинський, О.О. (Physico-technological Institute of Metals and Alloys, 2023)
Standard ductile cast iron grades do not always meet the ever-increasing materials requirements for creating of modern technique. Different countries of the world (USA, Germany, UK, Netherlands, France, etc.) are conducting research aimed at the development of scientific ideas and principles of microheterogeneous melts structure, optimization of processes of their modifying and structure formation at crystallization for increasing of technological and performance properties of ductile cast iron. The results of such research are relevant and allow obtaining of ductile cast iron products with unique performance characteristics. Today silicon alloyed ductile irons are widely used, which have high tensile strength and elongation and are well machined. The article presents the results of research on the effect of melt alloying with silicon (in the amount of 3.0 up to 4.0 wt.%) and nickel (up to 1.0 wt.%) on structure formation and mechanical properties of ductile cast iron with nodular graphite modified in the foundry mold. It is established that an increasing of silicon amount in the melt from 3.0 to 4.0 wt. % at 0.5 wt.% of nickel increases the ferrite amount in the castings structure as well as, at 30 % (in average) the tensile and yield strength compared to ductile cast iron that is not nickel-alloyed. Ductile cast irons containing from 3.5 to 4.0 wt.% of silicon and alloyed with ~1.0 wt.% of Ni in cast products have mechanical properties at the level of Rm ≥ 650 MPa, Rp0,2 ≥ 530 MPa, A ≥ 14 %. An important advantage of such ductile irons is a more uniform distribution of mechanical properties and hardness in castings, improving their machinability. The combination of these indicators significantly increases the quality of ductile iron castings and their competitiveness.